Barriers and facilitators to the implementation of the advanced nurse practitioner role in primary care settings: A scoping review. (April 2020) - Torrens, Claire; Campbell, Pauline; Hoskins, Gaylor; Strachan, Heather; Wells, Mary; Cunningham, Maggie; Bottone, Hannah; Polson, Rob; Maxwell, Margaret
Abstract: Background: Workload and workforce issues in primary care are key drivers for the growing international trend to expand nursing roles. Advanced nurse practitioners are increasingly being appointed to take on activities and roles traditionally carried out by doctors. Successful implementation of any new role within multidisciplinary teams is complex and time-consuming, therefore it is important to understand the factors that may hinder or support implementation of the advanced nurse practitioner role in primary care settings. Objectives: To identify, appraise and synthesise the barriers and facilitators that impact implementation of advanced practitioner roles in primary care settings. Methods: A scoping review conducted using the Arksey and O'Malley (2005) framework and reported in accordance with PRISMA-ScR. Eight databases (Cochrane Library, Health Business Elite, Kings Fund Library, HMIC, Medline, CINAHL, SCOPUS and Web of Science) were searched to identify studies published in English between 2002 and 2017. Study selection and methodological assessment were conducted by two independent reviewers. A pre-piloted extraction form was used to extract the following data: study characteristics, context, participants and information describing the advanced nurse practitioner role. Deductive coding for barriers and facilitators was undertaken using a modified Yorkshire Contributory Framework. We used inductive coding for barriers or facilitators that could not be classified using pre-defined codes. Disagreements were addressed through discussion. Descriptive data was tabulated within evidence tables, and key findings for barriers and facilitators were brought together within a narrative synthesis based on the volume of evidence. Findings: Systematic searching identified 5976 potential records, 2852 abstracts were screened, and 122 full texts were retrieved. Fifty-four studies (reported across 76 publications) met the selection criteria. Half of the studies ( n = 27) were conducted in North America ( n = 27), and 25/54 employed a qualitative design. The advanced nurse practitioner role was diverse, working across the lifespan and with different patient groups. However, there was little agreement about the level of autonomy, or what constituted everyday activities. Team factors were the most frequently reported barrier and facilitator. Individual factors, lines of responsibility and 'other' factors (i.e., funding), were also frequently reported barriers. Facilitators included individual factors, supervision and leadership and 'other' factors (i.e., funding, planning for role integration). Conclusion: Building collaborative relationships with other healthcare professionals and negotiating the role are critical to the success of the implementation of the advanced nurse practitioner role. Team consensus about the role and how it integrates into the wider team is also essential.